Land use efficiency of castor (Ricinus communis L.) based cropping systems in Okigwe, Southeastern Nigeria - Ikeh, Angus Onwudiwe; Amulu, Leonardo Uzoma; Orji, Janet Oliver; Olufelo, Olushola Joseph; Umelo, Queen Chidinma (Applied Research in Science and Technology, 2023)
Field study was carried out at Umuowa Ibu1 via National Horticultural Research Mbato Okigwe Imo state, Nigeria, to evaluate the effect of cropping systems on growth and yield of castor southeastern Nigeria. The experiment was laid in a randomized complete block design. The treatments were nine castor based cropping systems. Data collected were subjected to analysis of variance. Significant means were compared with LSD at 5% probability level. Result showed that castor seed yield was influenced by cropping systems. Significant castor yield was recorded in the treatment of sole castor with 1289.34 and 1286.77 kg/ha in both cropping seasons, followed by 1288.43 and 1280.44 kg/ha recorded in castor + cowpea intercrop. The yield obtain from sole castor was not significant difference when compared to yield obtained from castor + cowpea and also in the treatment of castor + groundnut intercrop. The least castor seed yield; 1002.23 and 1007.23 kg/ha was recorded in castor + groundnut + garden egg intercrop. The yield of component crops decreases as number of crops in the systems progressed from two to three. Castor + cowpea + pepper cropping system had the highest land equivalent ratio (LER); 5.62 and 5.63 in both cropping seasons. The least LER: 2.23 and 2.24 was recorded in castor + groundnut treatment. Castor based cropping system with cowpea and pepper was recommended for higher land use efficiency.